The effects of heat treatment at temperatures of 1100 °C to 1300 °C on the tensile properties of high-strength drawn tungsten fibres. (August 2018) - Müller, A. v.; Ilg, M.; Gietl, H.; Höschen, T.; Neu, R.; Pintsuk, G.; Riesch, J.; Siefken, U.; You, J.H.
Highlights: Investigations regarding the effect of heat treatments on the properties of high-strength W fibres are presented. Results of single fibre tensile tests, SEM microstructure investigations as well as chemical composition analyses are discussed. The performed investigations indicate that small amounts of impurities incorporated into the material can lead to a significant deterioration of the W fibre mechanical properties. Abstract: The design and manufacture of highly heat loaded plasma-facing components (PFCs) represents a major challenge for the realisation of thermonuclear magnetic confinement fusion. The performance of such PFCs is essentially related to the properties of the materials that are used for their design. Currently, tungsten fibre-reinforced metal matrix composites (MMCs) are regarded as promising advanced materials for PFC applications. In this respect, tungsten fibre-reinforced tungsten is being investigated as an advanced pseudo-ductile plasma-facing material while tungsten fibre-reinforced copper is being developed as an advanced heat sink material. The essential ingredients for the abovementioned MMCs are the fibrous reinforcements which are commercially available drawn tungsten fibres. An important aspect regarding the development of the abovementioned MMCs is the effect of the composite material manufacturing process on the properties of these high-strength reinforcements. During composite material manufacturing experiments it has been found that the mechanical properties of the used W fibres can be deteriorated significantly already at process temperatures of approximately 1200 °C. Against this background, dedicated investigations have been conducted on drawn tungsten fibre samples. In more detail, single fibre tensile tests, microstructural investigations as well as chemical composition analyses have been conducted. All in all, the performed investigations indicate that impurities incorporated into the tungsten fibre material are the underlying reason for the observed deterioration of the mechanical properties.